Investigation of a longfin inshore squid's swimming characteristics and an underwater locomotion during acceleration - Malazi, Mandi Tabatabaei; Olcay, Ali Bahadir (ELSEVIER SCI LTD, 2016)
In the present study, locomotion of a real longfin inshore squid (Doryteuthis pealeii) was numerically investigated. Geometry of a real squid was obtained using computed tomography (CT) images. In addition to a two-dimensional axisymmetric squid model, a modified squid model with no cavities around her head and an ellipse shaped model were generated with a fineness ratio (the ratio of body length to maximum body diameter) of 7.56. These numerical models were exposed to an acceleration with two different velocity programs. Added mass and basset forces on bodies were calculated during acceleration of the squid models starting from rest. Pressure and viscous drag forces were also calculated due to pressure variation along the squid models and friction on the surface of the models. The effect of a nozzle diameter on jet velocities and propulsive efficiency at all bodies were evaluated when time dependent velocity profiles (from 0 to 10 m/s in 0.5 and 1 s time durations) were set for the inlet of computational domain. The modified squid model required least thrust force during acceleration phase of time dependent velocity profile compared to the other models while the 0.02 m nozzle diameter provided largest propulsive efficiency for all models. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Longfin inshore squid; Computed tomography (CT); CFD; Propulsive efficiency; Drag; Unsteady fluid flow; MODELS; BODY; Engineering; Oceanography